Handbook of Marriage and the Family - Peterson, Gary W.; Bush, Kevin R. (Springer, 2013)
Before describing the history, purpose, and structure of this book, it seems appropriate to identify an unintentional and latent theme in this Handbook of Marriage and the Family, 3rd Edition . As we edited these excellent chapters, a covert theme seemed to emerge in this immense amount of knowledge that explains why people seek to live in the diversity of family forms and close relationships described in this book. An essential theme that courses through these pages is that families, in their various forms, may be the primary means to address two fundamental interpersonal relationship needs: connection and autonomy. Reduced to their essence, family members, following the human inclination for social bonding, seek to address the elemental relationship question: “How to balance one’s needs for connections with others while, at the same time, af fi rming one’s individuality within their interpersonal relationships?”
Keywords: Family; Marriage